EFFECT OF AUDIT ROTATION, AUDIT COMMITTEE, AND AUDITOR SPECIALIZATION ON AUDIT QUALITY - Nurfaadila, Yasmin; Deliana, Deliana; Afriani, Selfi; Syahputra, Rizki (Jurnal Kajian Akuntansi dan Auditing, 2026)
This study aims to examine the effect of audit rotation, audit committee, and auditor specialization on audit quality in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employs secondary data obtained from the companies’ annual reports and the official website of the Indonesia Stock Exchange. The sampling technique used is purposive sampling. Based on the predetermined criteria, 81 companies were selected as the sample with a five-year observation period, resulting in a total of 405 observations. Data were collected through the documentation method and analyzed using logistic regression with the assistance of SPSS version 27. The results indicate that audit rotation does not have a significant effect on audit quality. Meanwhile, the audit committee has a positive effect on audit quality. Auditor specialization also shows a positive and significant effect on audit quality in financial sector companies listed on the Indonesia Stock Exchange.